GENETIC FAMILIES OF LATE PRECAMBRIAN AND CAMBRIAN OILS (NAPHTHIDES) IN THE EAST SIBERIAN PLATFORM - Kashirtsev V.A. (My University, 2004)
Two genetic families of "ancient" oils, the main currently prospected resources, are known on the Siberian Platform. The available information on organic geochemistry of naphthide deposits and syngenetically bituminized sequences in the east of the platform permits recognition of two additional genetic families to which rather large deposits of oil can be related.
Keywords: Sedimentary formations; naphthide formation; biomarker molecules; isotopic composition of hydrocarbons; Siberian Platform; Cambrian; Precambrian; Paleozoic::Cambrian; Докембрий; Precambrian; Палеозой::Кембрийская